Errors and Their Causes in Solving One-Variable Linear Equations Among Mexican High School Students - Morales-Benitez, Leineri; Salgado-Beltrán, Gerardo; Son, Aloisius Loka; García-García, Javier (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
The aim of this study was to identify the errors made by a group of Mexican High School students when solving linear equations, as well as their possible causes. Data collection was conducted through a task-based interview administered to 30 students from a public school in southern Mexico. The results revealed that students made arithmetic errors when solving linear equations, including difficulties in performing operations with integers, handling fractions, applying the distributive property, and transposing terms incorrectly. By analyzing students' reasoning, it was inferred that these errors stem mainly from poor assimilation of arithmetic concepts, affective and emotional factors, and the presence of cognitive obstacles. Additionally, both procedural and conceptual algebraic errors were identified. According to the conceptual framework, these errors originate from limited manipulation of algebraic language, incorrect application of procedural rules, and didactic and cognitive obstacles. These findings encourage reflection on future research aimed at improving the learning of linear equations at the high school level.